The Rhetorical Functions of Citations in the Discussion Sections of Two Articles in Journal of English for Academic Purposes - Putri Karamina; Siti Wachidah (Stairs, 2021)
This study aims to examine the transitivity system of rhetorical functions in the Discussion section of two articles in the Journal of English for Academic Purposes by investigating the type of processes used in the rhetorical functions and how each type of process is represented in the English lexicogrammatical system. The data for this qualitative study were collected through genre analysis on two articles on citation practices from the Journal of English for Academic Purposes. The study found that comparison with sources and attribution were the most prominent rhetorical function within the Discussion section and that in comparison with sources, verbal processes were the most dominant type of processes, followed by relational, material, and mental processes, while in attribution, relational processes were the most used type of process, with material, verbal, and mental processes following behind. The findings of the study also showed that both comparison with sources and attribution were equally important in the Discussion section.